Implementation, Success And Challenges Of The Omsc Learning Continuity Plan : From The Lens Of Faculty - Muyot, ChE, EdD, Norma B.; Edaniol, EdD, Elbert C. (International Journal of Educational Research & Social Sciences, 2022)
The COVID-19 pandemic has had a profound and rapid impact on higher education institutions across the world resulting from the lockdowns and movement restrictions which resulted to cancellation of face to face classes and necessitated the crafting and implementation of a learning continuity plan. This study focused on the extent of the implementation, success and challenges of the OMSC Learning Continuity Plan viewed from the lens of the faculty members. The qualitative-quantitative approach and Reflective Cycle design were used to gather and give meaning to the experiences of the faculty as the plan was implemented. A questionnaire was used to gather data and virtual focus group discussions were conducted to contextualize the narratives of the respondents. Results of the study indicate that the faculty believe that LCP was highly implemented in terms of its four majors components of: instructional management and supervision, human resource development, learning resource development and delivery and safety and conducive learning environment. Moreover, the LCP was highly successful in terms of attainment of learning outcomes, resource mobilization; and equity in access to learning resources. Finally, the common challenges encountered by the faculty members in the implementation of the LCP were: limited access to internet and unstable internet connection, difficulty in assessing performance-based tasks and related learning experience especially laboratory subjects, difficulty in tracking, checking student’s outputs especially for large class sizes in online modality, late submission of students’ outputs particularly those in modular distance learning, dissertation/Thesis defense schedule could not be fixed due to students’ connectivity problems and students’ inability to participate in group activities.